Human Rights and the Environment - Glazebrook, Susan (Victoria University of Wellington Law Review, 2009)
Justice Glazebrook, in this article, addresses the basic questions whether there is a human right to an environment of good quality and whether that right should be part of a Pacific human rights mechanism. If there is no such right, the question of whether there should be is addressed.